2000
DOI: 10.1007/s004230000146
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic hepatic wedge resection of hemangioma: report of two cases

Abstract: This paper describes two cases of hepatic cavernous hemangiomas, both of which were removed laparoscopically. No blood transfusion was necessary. No surgical complications occurred and the patients were discharged on the second postoperative day. We conclude that, depending on the size and location of the tumor, laparoscopic resection of liver hemangiomas can be performed safely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
(18 reference statements)
0
17
0
Order By: Relevance
“…Thus, multicenter clinical trials are desirable to confirm these promising results. In view of the results of this and other studies [1][2][3][4], we suppose that laparoscopic hepatectomy will become a popular technique for the treatment of benign and malignant liver lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, multicenter clinical trials are desirable to confirm these promising results. In view of the results of this and other studies [1][2][3][4], we suppose that laparoscopic hepatectomy will become a popular technique for the treatment of benign and malignant liver lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In 1991, Reich et al [7] firstly reported on laparoscopic hepatectomy, thereby arousing the interest of many surgeons in this field. Since then laparoscopic hepatic resection techniques have been developed and special devices have been supplied, and laparoscopic hepatectomy has been becoming a more common procedure for the treatment of benign and malignant liver lesions [1][2][3][4]. The most important technique in laparoscopic hepatectomy is liver parenchymal transection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether the dierences in the stress and immune response lead to dierent outcomes in oncological surgery, especially regarding long-term survival, is still under discussion. Laparoscopic liver resections have been performed in only a few hospitals since 1995, and some articles have been published on this topic [2,6,23,25]. Prospective data on the advantages of laparoscopic liver resection have not been published.…”
Section: Introductionmentioning
confidence: 95%
“…Successful laparoscopic liver biopsy procedures have been reported for a number of small series, mainly with the use of laparoscopic coagulating shears (Harmonic scalpel TM , Ethicon Endo-Surgery, CVG, Cincinnati, Ohio) or a vascular liner stapler [1,11]. However, successful larger laparoscopic hepatic resections have recently been reported in adults [5,7,11].…”
Section: Introductionmentioning
confidence: 98%